2013
DOI: 10.1097/icl.0b013e31828af164
|View full text |Cite
|
Sign up to set email alerts
|

Tear Lipid Layer and Contact Lens Comfort

Abstract: This review describes the impact of contact lens wear on the tear film lipid layer and how changes in the lipid layer might modulate contact lens-related discomfort. Relevant clinical, functional, and biochemical aspects of the tear film lipid layer are reviewed. Contact lens wear modulates these aspects of the lipid layer, specifically the prelens lipid layer thickness is reduced; tear evaporation rate is increased; tear breakup time is reduced; and the concentration of lipid components such as cholesterol es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Also, tear evaporation rate from the corneal surface only was measured but not from the entire exposed ocular surface, possibly excluding the evaporation rate from the lens edge. Tear evaporation rates in the present study are comparable to the previous reports and the relative change in evaporation rate with contact lens wear in our study is about 1.6 times, which falls within the range of previously reported values …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, tear evaporation rate from the corneal surface only was measured but not from the entire exposed ocular surface, possibly excluding the evaporation rate from the lens edge. Tear evaporation rates in the present study are comparable to the previous reports and the relative change in evaporation rate with contact lens wear in our study is about 1.6 times, which falls within the range of previously reported values …”
Section: Discussionsupporting
confidence: 92%
“…Tear evaporation rates in the present study are comparable to the previous reports and the relative change in evaporation rate with contact lens wear in our study is about 1.6 times, which falls within the range of previously reported values. 35 In the current study, tear evaporation rates with and with no lens wear conditions showed a significant direct association. This finding indicates that an individual's tear film characteristics rather than a lens might be an overriding influence on tear film evaporation.…”
Section: Discussionsupporting
confidence: 45%
“…Contact lens wear disrupts the tear lipid layer, causing increased tear evaporation and a lower tear breakup time (see the review by Rohit and colleagues 300 ), supporting the Dry Eye WorkShop 301 classification of contact lens dry eye as due to evaporative causes. Increased tear evaporation from the front surface of the lens is not necessarily accompanied or followed by overt corneal damage under the contact lens; however, thin high-water content lenses do reportedly cause pervaporation from the post-contact lens tear film and subsequent corneal staining.…”
Section: Desiccationmentioning
confidence: 86%
“…After 2 to 4 weeks of daily wear and according to the manufacturer instructions, enhanced-lotrafilcon A and enhanced-lotrafilcon B contact lenses showed significantly lower cholesterol sorption than balafilcon A, comfilcon A, enfilcon A, galyfilcon A, and senofilcon A lenses (P,0.0001 for all comparisons). [29][30][31] Therefore, it is all the more interesting that cholesterol has been demonstrated to be the most predominant lipid component of the tear film lipids. 10 Moreover, the outer lipid layer, which is widely believed to form an interface with the air interface of the tear film, is hypothesized to play a critical role in preventing evaporation of the tear film and, more generally, an important structural role for a healthy tear film.…”
Section: Discussionmentioning
confidence: 99%